Funastrain c II: A Cysteine Endopeptidase Purified from the Latex of Funastrum clausum - Morcelle del Valle, Susana Raquel (2004)
A cysteine endopeptidase, named funastrain c II, was isolated and characterized from the latex of Funastrum clausum (Asclepiadaceae). The molecular mass (mass spectrometry) of the protease was 23.636 kDa. The analysis of funastrain c II by SDS-PAGE revealed a single polypeptide chain. The enzyme showed a remarkable stability of its caseinolytic activity after incubation at temperatures as high as 70°C. Inhibition and activation assays indicated the cysteinic nature of the funastrain c II catalytic site. The optimum pH of funastrain c II enzymatic activity varied according to the substrate used (9.0–10.0 for casein and 6.2–6.8 for PFLNA). Kinetic parameters were determined for N-α-CBZ-Ala p-nitrophenyl ester (Km = 0.0243 mM, kcat = 1.5 s–1) and L-pyroglutamyl-L-phenylalanyl-L-leucine-p-nitroanilide (PFLNA; KM = 0.1011 mM, kcat = 0.9 s–1). The N-terminal sequence of funastrain c II showed considerable similarity to other proteases isolated from latex of different Asclepiadaceae species as well as to other cysteine proteinases belonging to the papain family.